Enantioselective Total Synthesis of Multifidene, a Sex Pheromone of Brown Algae - Taiki Umezawa; Misaki Hara; Nana Kinoshita-Terauchi; Fuyuhiko Matsuda (Organics, 2022)
The total synthesis of multifidene, a sex pheromone found in brown algae, is described. The synthesis features the highly enantioselective and diastereoselective addition reaction of an aldehyde to a nitroolefin in the presence of a Hayashi–Jørgensen catalyst and a Nef reaction initiated by visible light irradiation. These key reactions enabled the 11-step synthesis from commercially available compounds. The synthetic pheromones are examined with gametes.